Aligning Policy For Success In Developing Countries: Evidence From The Poultry Sector Of Ghana. - Zamani, O.; Chibanda, C.; Boimah, M.; Asante‑Addo, C. (Agricultural and Food Economics, 2025)
This paper examines policy coherence in Ghana’s poultry sector by assessing potential interactions between policy objectives. Using panel simultaneous equation models and the data-driven synthetic control method, we analyze the efects of policy inter‑ ventions on domestic poultry production during 1999–2019. Our fndings underscore the impact of policies enacted during this period on the growth of domestic poultry production. However, growth in production remains notably lower than the escalating imports of frozen poultry meat. Our coherence analysis identifes lowering produc‑ tion costs and enhancing productivity as crucial policy objectives that could positively afect food security and rural development. Nonetheless, we caution against prioritiz‑ ing one objective over others, as this may adversely afect overall policy coherence and outcomes. Specifcally, our study emphasizes the importance of striking a balance between fostering domestic production and ensuring food security.
Research Article
Keywords: Policy coherence; Synergies; Synthetic Control Method; Poultry; Ghana